Prevalence of asthma, allergic rhinitis and eczema in 6–7-year-old schoolchildren from Luanda, Angola - Arrais, Margarete (2019)
Background: Epidemiological data have shown that the prevalence of asthma, rhinoconjunctivitis and eczema in children is still increasing, namely in Africa. However, there are no epidemiological studies on asthma or allergic diseases in Angolan children. Objective: To study the prevalence of asthma and other allergic diseases in Angolan children. Methods: Descriptive, observational, cross-sectional study, using the ISAAC study methodology, in the province of Luanda, Angola in 6-7-yearold children. Forty-six (8.3%) public schools were randomly selected. Data were analysed using the SPSS Statistics version 24.0 software. Results: A total of 3080 children were studied. Results showed that the prevalence of asthma (wheezing in the previous 12 months) was 15.8%, that of rhinitis (sneezing, runny or blocked nose in the previous 12 months) was 19% and that of eczema (itchy skin lesions in the previous 12 months) was 22%, without differences between sexes. Rhinitis was associated with a higher number of episodes of wheezing episodes, disturbed sleep and night cough, in children with asthma. Rhinitis, eczema, Split-type air conditioning system, antibiotic intake in the child's first year of life, frequent intake (more than once per month) of paracetamol and active maternal smoking were associated with a higher risk of having asthma, whereas electrical cooking was associated with a protective effect. Conclusion: Asthma and allergic diseases are highly prevalent in children from Luanda. A strategy for preventive and control measures should be implemented.